Transitional Justice and Theories of Change: Towards evaluation as understanding. (21st July 2020) - Gready, Paul; Robins, Simon
Abstract: This article has two goals. First, to make explicit the theories of change currently operative within transitional justice and, second, to critically engage with both these theories, and dominant theories in international development. As such, it seeks to replace a focus on results, attribution, and linearity with a privileging of process, contribution and complexity. Developing theories of change for transitional justice is challenging, as it is characterised by diverse interventions, complex and contested contexts, and the need to balance principles and pragmatism. Normative, linear and mechanism-based claims remain dominant, while the evidence base for transitional justice is still weak. This article looks at insights from adjacent fields, some of the challenges facing the development of theories of change within transitional justice, and evidence from impact studies and evaluations. In a final section we propose an alternative, drawing on complexity theory and actor-oriented approaches, which suggest an important set of terms – systems, interaction, contingency, context, encounter, emergence, incrementalism – to inform what we term evaluation as understanding.